Swing Time [videorecording (DVD)] - Stevens, George, 1904-1975; Astaire, Fred; Rogers, Ginger, 1911-1995; Moore, Victor, 1876-1962 (American Film Institute series., 2005)
A performer and gambler travels to New York City to raise the $25,000 he needs to marry his fiancée, only to become entangled with a beautiful aspiring dancer.